Caracterização química da casca de pequi (Caryocar brasiliense Camb.), avaliação de seus extratos e aplicação em linguiça de frango para aumento do shelf life - Monteiro, Sabrina Sauthier (2013)
The present study aimed to evaluate the extraction of phenolic in pequi peel (Caryocar brasiliense Camb.) by the methods of agitation and microwave focusing and subsequent application of the extract with the highest yield in fresh sausages to prolong shelf life. Analyzes were performed to obtain the chemical composition of pequi peel and extracts were quantified in the total phenolic content and antioxidant activity by DPPH method and β-carotene / linoleic acid system test. The hydroethanolic extract 80% submitted to agitation of the pequi peel showed the greater phenolic content and was applied at concentrations of 0.5%, 1.0% and 1.5% (w / v) in the manufacture of chicken sausage and subsequently analyzed in cold storage at 4 ° C for 42 days. Analyses of moisture, protein, ash and fat in sausages were analyzed every seven days for pH, color, TBARS values and microbiological analyzes. Sensory analysis was assessed by testing the acceptability hedonic scale with seven points and calculated index of acceptability. The results on the chemical composition of the products are in compliance with required by Brazilian law. With regard to the color of the product, this showed a trend toward dark staining during storage. In the final period of storage the amount of TBARS sausage to 1.5% of extract was 0.10 ± 0.421 mg MDA.Kg-1 sample and control 1.375 ± 0.11 mg MDA.Kg-1. The values for coagulase positive Staphylococcus, Salmonella, Coliform bacteria and fecal coliforms were below the limits established by law. The rate of acceptability (% IA) for the attributes analyzed had a satisfactory initial panel test except for color, odor and appearance of the product with the highest concentration of the extract. It is concluded that the sausages prepared with this extract at a concentration of 1.0% showed satisfactory results when it is to prolong shelf life.